2000
DOI: 10.1021/np000094q
|View full text |Cite
|
Sign up to set email alerts
|

Vertilecanins:  New Phenopicolinic Acid Analogues from Verticillium lecanii

Abstract: Five new phenopicolinic acid analogues (1-5) have been isolated from solid-substrate fermentation cultures of Verticillium lecanii. The most abundant component (vertilecanin A; 1) displays antiinsectan activity against Helicoverpa zea. These compounds were obtained by chromatographic fractionation of the EtOAc culture extract and identified by analysis of NMR and MS data. The known fungal metabolites 2-decenedioic acid and 10-hydroxy-8-decenoic acid were also isolated from these cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 13 publications
0
34
0
Order By: Relevance
“…Many nematode-antagonistic fungi produce secondary metabolites and enzymes that demonstrate toxicity against plant-parasitic nematodes Meyer et al, 2004;Nitao et al, 1999Nitao et al, , 2001Nitao et al, , 2002Anke et al, 1995;Hallmann and Sikora, 1996;Bonants et al, 1995), and it was hypothesized that V. lecanii produced a natural substance that could affect egg viability (Meyer and Wergin, 1998). While it has been reported that certain insecticidal secondary metabolites or enzymes are produced by V. lecanii (Kanaoka et al, 1997;Soman et al, 2001;Wang et al, 2005;Butt, 2002;Claydon and Grove, 1982;Jackson et al, 1985;Liu et al, 2003), secondary metabolites or enzymes with nematode-antagonistic properties are not as well studied. Therefore, the purpose of this study is to evaluate the toxic effects of fungal culture filtrates of hybrid strains of V. lecanii on eggs and juveniles of SCN, and to compare the toxicity of the hybrid strains with that of their parental strains.…”
Section: Introductionmentioning
confidence: 99%
“…Many nematode-antagonistic fungi produce secondary metabolites and enzymes that demonstrate toxicity against plant-parasitic nematodes Meyer et al, 2004;Nitao et al, 1999Nitao et al, , 2001Nitao et al, , 2002Anke et al, 1995;Hallmann and Sikora, 1996;Bonants et al, 1995), and it was hypothesized that V. lecanii produced a natural substance that could affect egg viability (Meyer and Wergin, 1998). While it has been reported that certain insecticidal secondary metabolites or enzymes are produced by V. lecanii (Kanaoka et al, 1997;Soman et al, 2001;Wang et al, 2005;Butt, 2002;Claydon and Grove, 1982;Jackson et al, 1985;Liu et al, 2003), secondary metabolites or enzymes with nematode-antagonistic properties are not as well studied. Therefore, the purpose of this study is to evaluate the toxic effects of fungal culture filtrates of hybrid strains of V. lecanii on eggs and juveniles of SCN, and to compare the toxicity of the hybrid strains with that of their parental strains.…”
Section: Introductionmentioning
confidence: 99%
“…1 We suppose that this synthetic approach can be a versatile methodology for the preparation of different pheno picolonic acid derivatives.…”
mentioning
confidence: 99%
“…In a report, 42 strains of marine bacterial isolates showed antimicrobial activity and were assigned to genera Alteromonas , Pseudomonas , Bacillus and Flavobacterium [107]. Certain mycoparasitic and fungicolous fungi are known to colonize other fungal physiological structures and are known to be the source of effective bioactive agents [108–111]. A study conducted in the United States in 2002 reported five new natural products, Phomadecalins A, B, C and D, and Phomapentenone A, from cultures of Phoma sp.…”
Section: Marine Microorganisms As Producers Of Bioactive Compoundsmentioning
confidence: 99%